Konsep Pendidikan Anak dalam Hadis Nabi SAW (Kajian Ma’anil Hadis Sunan Ibn Majah No.3661) - Agung Setiyawan (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2015)
Hadith of Sunan Ibn Majah, Book of Al-Adab, Chapter of Birr Al-Wahid Aa Al- Hasan Ila Al-Banat, verse 3661 discussess the children education as exemplified by Prophet Muhammad SAW. This research utilizes various assessment approaches including linguistic linguistic analysis, a comprehensive thematic assessment, confirmatory study, historical reality analysis, generalization and practical criticism analysis. The results showed that generally, there are two main lessons being delivered which are the order of dignifying children and improving their education. However, this hadith provides specific lessons, including the reasons of dignifying children and educating them through the understanding of the Al qur’an verses and the thematic Hadith, the principals of educating children, also the benefits and the use of this hadith in addressing various educational issues related to parents and children.